1980
DOI: 10.1073/pnas.77.1.588
|View full text |Cite
|
Sign up to set email alerts
|

Crohn disease lymph node homogenates produce murine lymphoma in athymic mice.

Abstract: To study the putative agent(s) related to Crohn disease, we intraperitoneally in injected mesenteric lymph node homogenates from four patients with active Crohn disease into 10-week-old athymic (nu/nu) mice. Control mice (nu/nu) were injected with homogenates of mesenteric lymph nodes from two patients with ulcerative colitis and four patients undergoing elective cholecystectomy, and with a homogenate of a cervical lymph node containing sarcoid granuloma. Thirty-four mice received filtered or unfiltered homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1981
1981
2000
2000

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Of note, most non-transplant studies have demonstrated that immunosuppression related NHL does not show the same predilection for the brain as those in transplant recipients. Furthermore, in the setting of immunosuppression, it is interesting to note that Crohn's tissue homogenates have been reported to induce B cell lymphomas in athymic mice suggesting, at least in experimental animals, a link between Crohn's disease, immunosuppression, and malignant lymphoma 41. In addition, three of our four cases were large cell diffuse B cell lymphomas, which are by far the commonest type of immunosuppression induced lymphoma described 42…”
Section: Discussionmentioning
confidence: 65%
“…Of note, most non-transplant studies have demonstrated that immunosuppression related NHL does not show the same predilection for the brain as those in transplant recipients. Furthermore, in the setting of immunosuppression, it is interesting to note that Crohn's tissue homogenates have been reported to induce B cell lymphomas in athymic mice suggesting, at least in experimental animals, a link between Crohn's disease, immunosuppression, and malignant lymphoma 41. In addition, three of our four cases were large cell diffuse B cell lymphomas, which are by far the commonest type of immunosuppression induced lymphoma described 42…”
Section: Discussionmentioning
confidence: 65%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], and 314 mice euthanatized at 5 months (Nos. 2 1-23) appeared healthy.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In a multicenter study in which various investigators exchanged material, a transmissible histologic abnormality could not be reproduced (272). In recent years, Das et al (69) have described the production of lymphomas or plasma cell hyperplasia in nude mice by the injection of Crohn's disease tissue. Also, these authors claim that sera from Crohn's disease patients react with certain cells or cell types in these murine lymphomas as demonstrated by the fluorescent-antibody technique (13,301,310).…”
mentioning
confidence: 99%